Is routine MRI necessary to exclude pathological fractures in patients with an oncological history? - Seng, Daniel Wei Ren; Kwek, Ernest Beng Kee (Archives of orthopaedic and trauma surgery, 2018)
Introduction Magnetic resonance imaging (MRI) is the radiological modality of choice for diagnosing pathological fractures in situations of diagnostic uncertainty. With the increasing availability of MRI, we have observed a disturbing trend in utilising routine MRI scans to exclude pathological fractures in all patients with a history of cancer. The study objective was to determine if routine use of MRI scans in such patients is truly necessary and if other predictive factors can be utilised in lieu of the MRI scan. Materials and methods A 3-year retrospective study was conducted reviewing all extremity MRI scans performed for suspected pathological fractures and compared to X-rays. All patients presented with an extremity fracture, a known diagnosis of solid organ cancer and had an MRI to determine if the fracture was pathological. Subjects were followed up with serial X-rays up to 1 year. Results 84 subjects were recruited. Comparing X-rays alone with MRI scans revealed 92% sensitivity and 98% specificity in detecting pathological fractures. Using X-rays in combination with an absent history of trauma increases the sensitivity to 100% but reduced the specificity to 91%. None of subjects in cancer remission had pathological fractures. Conclusions MRI is an imperative tool for operative planning in pathological fractures; however, we recommend against the routine use of MRI to diagnose pathological fractures in oncological patients. Patients with solid organ cancer remission, a positive history of significant trauma prior to sustaining the fracture, and the absence of pathological features on plain radiographs are strongly predictive against pathological fractures.